Seventy-five years West German currency reform: Crisis as catalyst for the erosion of the market order - Gunther Schnabl (Kyklos, 2023)
The paper analyzes the role of the 1948 currency and economic reform in West Germany for growth and social cohesion in Germany and Europe. It describes the theoretical foundation by Walter Eucken and the implementation and defense of the new economic order by Ludwig Erhard. The paper stresses the positive impact of the market economy on growth and welfare in Germany and Europe. Then, it is shown that Eucken's constituting principles of the market economy were gradually eroded after euro introduction in course of crises, with the negative repercussions on growth and equality being explained. The policy conclusion is that only the reconstitution of price stability in the euro area can prevent a further decline of welfare in Europe. The 1948 economic reforms provide an important blueprint for the necessary reform process.
Keywords: 300